The genetic characterization of Curvularia tuberculata fungus isolates isolated from rice crop grains in Al Diwania city - Ebtesam thamer jeaz; Majed kadem abod (Al-Qadisiyah Journal of Pure Science, 2017)
This study characterization of some types of Curvularia spp . isolated frome rice seeds in AL Diwaniya city by morphological ,microscopical and genetical characterization of these isolates. The results by morphological and microscopical characteristics showed one type of Curvularia spp. Is C. tuberculata with( 9) isolates, with(1) isolate frome treated rice grains with percentage 0.3% , while (8) isolates frome untreated rice grains with percentage 1.3% . The results multiplex PCR showed gpd gene in DNA of isolates investigated of C.tuberculata fungus .PH test showed higher growth rate of C. tuberculata fungus with (7.7) mm in ph (7) followed by (6.8) mm in ph (6) , (5.7) mm in ph (5 ,8 ) while decrease reach to (4.2) mm in ph (10) ,( 3.9, 3.1) mm in ph ( 3 , 6 ) ( the higher growth rate of fungus with neutral ecosyst ) .The higher growth rate of fungus with 20 gm / L concentration of Nacl salt reach to (8.5) mm while decrease reach to ( 6.4 , 5.2 , 4.5 ) mm with ( 5 , 10 , 15 ) gm / L concentrations ( the fungus tolerant to high concentrations of Nacl salt ) .